STUDI KRITIS POLIGAMI DALAM ISLAM (ANALISA TERHADAP ALASAN PRO DAN KONTRA POLIGAMI) - Siti Ropiah (Fakultas Agama Islam Universitas Wiralodra, 2018)
The discourse of polygamy in Islamic thought has become controversial and interesting to be discussed. Until now, polygamy as one form of marriage in Islam is still a debate. This kind of debate does not result anything in common because the argument of each opinion is based on Quranic verse An Nisa '(4): 3, 129, and hadith of the Prophet, as the highest source of law in Islam. The polygamy discourse can be divided into two opinions. First, support polygamy (pro polygamy) and secondly, against polygamy (contra polygamy).